Legal Protection for Children Perpetrators of Immoral Crime (Case Study Number 21/PID.SUS.Anak/2019/PN.Trg) - Alfian Rachmat Darmawan; Endah Lestari Dwirokhmeiti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Every child needs to get guidance and guidance from an early age because childhood is a period of shaping the personality, character and character of a human being, so that later they have the ability and strength and can be strong in life. The emotional instability of children tends to cause attitudes and actions that are considered naughty or known as juvenile delinquency. The protection policy for children in the Juvenile Criminal Justice System mandates that the judicial process is kept as far as possible from cases of children in conflict with the law. The fundamental substance regulated in Law Number 11 of 2012 concerning the Juvenile Justice System is strict rules regarding restorative and diversionary justice which are intended to prevent children from the judicial process.